1998
DOI: 10.1071/mf97089
|View full text |Cite
|
Sign up to set email alerts
|

Trophic function in estuaries: response of macrobenthos to natural and contaminant gradients

Abstract: Trophic ecology of macrobenthic communities in estuaries of the northern Gulf of Mexico was used to infer community function, determine effects of contaminants on macrobenthos, and provide insight into community responses following disturbance. The taxa that numerically dominated the region included few large, deep-burrowing suspension feeders that typify estuaries elsewhere. This pattern is indicative of disturbance, and results in dominance by trophic groups that live near the sediment–water interface (early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 0 publications
3
55
1
2
Order By: Relevance
“…All stations, except station 8, showed that molluscs were the dominant group, primarily M. falcata and M. guyanensis at the intertidal inner-bay stations and A. brasiliana at the subtidal station 10. This contrasted strongly with studies from the Gulf of Mexico estuaries (Gaston et al, 1998) showing crustaceans and gastropods as dominant in waters of high oxygen content (>2.0 mg.l -1 ) and polychaetes in low DO areas (<2.0 mg.l -1 ). M. guyanensis is able to survive in extremely adverse conditions and is tolerant of fluctuating salinities (Nishida & Leonel, 1995).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…All stations, except station 8, showed that molluscs were the dominant group, primarily M. falcata and M. guyanensis at the intertidal inner-bay stations and A. brasiliana at the subtidal station 10. This contrasted strongly with studies from the Gulf of Mexico estuaries (Gaston et al, 1998) showing crustaceans and gastropods as dominant in waters of high oxygen content (>2.0 mg.l -1 ) and polychaetes in low DO areas (<2.0 mg.l -1 ). M. guyanensis is able to survive in extremely adverse conditions and is tolerant of fluctuating salinities (Nishida & Leonel, 1995).…”
Section: Discussioncontrasting
confidence: 51%
“…4 or 7) (Tables 3 and 4). In contrast to what might have been expected (Harrel & Hall, 1991;Gaston et al, 1998;González-Oreja & Saiz-Salinas, 1998), the least diverse and most depauperated area (station 9) is located only 1 km from the richest and most diverse (station 10; Fig. 1; Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Mollusc diversity followed the salinity gradient, with the highest diversity in the downstream stations which were mostly influenced by marine intrusion, and decreasing towards upstream. Community composition gradually changes according to the salinity gradient of the lagoon, a trend similar to those reported in Gaston et al (1998) and Giberto et al (2004). Species (M. edulis, M. perna and C. gazar) known to be intolerant of wide fluctuations in salinity were restricted to station seven where a higher and relatively stable salinity was recorded, this observation has also been reported in other estuarine systems (Oyenekan, 1988).…”
Section: Discussionsupporting
confidence: 57%
“…Nonetheless, for this particular case three submetrics seem to be the most important: pollution indicative taxa, pollution sensitive taxa, and diversity. The subsurface deposit feeders species are considered the trophic group most likely to develop pollution tolerance (Gaston et al, 1998), since they inhabit tubes or burrow beneath the sediment surface (Pinn and Robertson, 2003). In the euhaline estuarine stations there was a relative increase of these species, followed by a diversity (H 0 ) increase and a decrease of the percentage abundance of pollution sensitive species.…”
Section: Benthic Index Of Biotic Integritymentioning
confidence: 99%